1983
DOI: 10.1139/b83-181
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation in high-arctic vascular plants of differing growth form

Abstract: Resource allocation strategies are described for a range of vascular plant species of a high-arctic lowland oasis, located adjacent to Alexandra Fjord, Ellesmere Island, N.W.T. The patterns of allocation of biomass and major nutrients (N, P, K, Ca, and Mg) differed greatly among the 16 species, which represented six growth forms (biennial herbs, perennial herbs, graminoids, cushion plants, deciduous dwarf shrubs, and evergreen dwarf shrubs). The dominant growth strategy was that of the stress tolerator, well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…The nitrogen concentrations we found in plants collected over 1 m from the muskox carcasses correspond well with average N concentrations reported for tundra plants Maessen et al, 1983) and for tundra mosses . Our carcasses were thus found in habitats with nitrogen levels typical of the tundra, and our results, although based on a small sample size, may have a general value.…”
Section: Discussionsupporting
confidence: 88%
“…The nitrogen concentrations we found in plants collected over 1 m from the muskox carcasses correspond well with average N concentrations reported for tundra plants Maessen et al, 1983) and for tundra mosses . Our carcasses were thus found in habitats with nitrogen levels typical of the tundra, and our results, although based on a small sample size, may have a general value.…”
Section: Discussionsupporting
confidence: 88%
“…The N and P concentrations found in the different ramet stages and plant parts were within the range previously found for C. bigelowii (Shaver and Chapin 1980;Carlsson and Callaghan 1990;JĂłnsdĂłttir and Callaghan 1990) and other rhizomatous tundra sedges (Massen et al 1983;Shaver et al 1998;Tolvanen and Henry 2000;Welker et al 2003). However, the differences in concentration between the guerrilla and phalanx types demonstrated in this study were not found in another C. bigelowii population close by that was also harvested in August (Carlsson and Callaghan 1990), possibly because different criteria were used to classify the ramet types (i.e., the developmental position of the ramets on their mother ramets, rather than rhizome length).…”
Section: Nutrient Concentrationsupporting
confidence: 86%
“…Due to these limitations in surface N availability, S. arctica may rely on subsurface N patches to satisfy midseason demands such as photosynthetic system maintenance, stem growth, and/or leaf storage (Maessen et al. , Baddeley et al. , Campioli et al.…”
Section: Discussionmentioning
confidence: 99%